The mysteries of Udolpho : a romance interspersed with some pieces of poetry - Radcliffe, Ann, 1764-1823 (Floating Press, 2009)
The Mysteries of Udolpho (1794) is the archetypal Gothic novel. A young woman, Emily St. Aubert, suffers the death of her father, followed by worsening physical and psychological death, mirrored in a landscape of crumbling castles and emotive Alps.